Corporate Governance Failures and Financial Statement Manipulation: Evidence from PT Asuransi Jiwasraya - Intan Juniarti; Rian Rusmana Putra; Rika Permatasari; Natasya Febriyanti (LPPM STIE KRAKATAU, 2026)
This study aims to analyze the relationship between Good Corporate Governance (GCG), financial statement quality, and corporate legal accountability from legal and accounting perspectives. This study is motivated by the importance of effective corporate governance as a tool for preventing financial statement manipulation and abuse of authority in corporate activities. This study uses normative legal research with a statutory and conceptual approach. Legal sources include legislation, legal doctrine, and scientific literature relevant to corporate governance and corporate criminal liability. The results indicate that the application of the principles of transparency, accountability, responsibility, independence, and fairness in GCG plays a crucial role in maintaining the integrity of financial statements. Weaknesses in internal control systems and compliance culture have the potential to cause distortions in financial information and the risk of legal violations. The national legal framework recognizes corporations as subjects of criminal law through the doctrine of corporate criminal liability and legislative provisions. The principles of fiduciary duty and the theory of fault serve as the basis for determining the legal liability of corporate bodies. The integration of corporate governance, transparency in financial reporting, and consistent law enforcement forms the foundation for creating an integrity-driven and sustainable corporate system. Regulatory reforms, accompanied by strengthened internal oversight and professionalism of law enforcement officials, are necessary to reinforce the stability of the economic sector and enhance public trust.